2012
DOI: 10.1371/journal.pone.0044787
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Role of Estrogen Receptor Beta as a Tumor Suppressor of Epithelial Ovarian Cancer

Abstract: Ovarian cancer is the gynecological cancer exhibiting the highest morbidity and improvement of treatments is still required. Previous studies have shown that Estrogen-receptor beta (ERβ) levels decreased along with ovarian carcinogenesis. Here, we present evidence that reintroduction of ERβ in BG-1 epithelial ovarian cancer cells, which express ERα, leads in vitro to a decrease of basal and estradiol-promoted cell proliferation. ERβ reduced the frequency of cells in S phase and increased the one of cells in G2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 55 publications
11
91
0
1
Order By: Relevance
“…Although the contradictory results might be due to cell-type specificity, our data are consistent with the observations in other cancer cells that ERa, but not ERb, plays a predominant role in the promotion of cell growth and survival (Thomas & Gustafsson 2011). While a few reports propose the proliferative and anti-apoptotic roles of ERb in cancer cells, the tumor suppressor properties of ERb have been demonstrated by the fact that overexpression of ERb results in anti-proliferative responses, whereas knockdown of ERb promotes the proliferative properties in different cancer cell types (Treeck et al 2007, 2010, Paruthiyil et al 2011, Bossard et al 2012. Moreover, a study of 24 OSCC specimens shows that the frequency of ERa expression (50%) is higher than that of ERb expression (33%) (Lukits et al 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Although the contradictory results might be due to cell-type specificity, our data are consistent with the observations in other cancer cells that ERa, but not ERb, plays a predominant role in the promotion of cell growth and survival (Thomas & Gustafsson 2011). While a few reports propose the proliferative and anti-apoptotic roles of ERb in cancer cells, the tumor suppressor properties of ERb have been demonstrated by the fact that overexpression of ERb results in anti-proliferative responses, whereas knockdown of ERb promotes the proliferative properties in different cancer cell types (Treeck et al 2007, 2010, Paruthiyil et al 2011, Bossard et al 2012. Moreover, a study of 24 OSCC specimens shows that the frequency of ERa expression (50%) is higher than that of ERb expression (33%) (Lukits et al 2007).…”
Section: Discussionsupporting
confidence: 83%
“…In support of our study showing the tumor suppressor role of ERβ, there are emerging evidences showing that ERβ has an anti-oncogenic role in the development and progression of some tumor types, including ovarian cancer, renal cell carcinoma, prostate cancer, and colon cancers. [23][24][25][26][27][28][29] Our study and these previous reports altogether indicated a protective role of ERβ in the development and progression of cancer.…”
supporting
confidence: 58%
“…Control (sh-Luc) and anti-AXL shRNAs were previously described (14). Luciferase-transfected MDA-MB-231 cells (MDA-MB-231-Luc) were previously described (16). RhGAS6 and the goat anti-human GAS6 antibody were purchased from R&D Systems.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Intraperitoneal treatments with 200 mg 20G7-D9/injection or saline were done twice a week for four consecutive weeks. Bone metastases were quantified by in vivo bioluminescence imaging at day 25, as described previously (16). For PDX models, approximately 60 mm 3 of B3804 and B3467 tumors were transplanted in the interscapular fat pads of Swiss nude female mice (Charles River Laboratories) and treated with 200 mg 20G7-D9 twice weekly or saline, when…”
Section: In Vivo Studiesmentioning
confidence: 99%